The prescribing pattern of obstructive airway disease medicines in outpatient pharmacy department, Hospital Tengku Ampuan Rahimah Klang / Tengku Norfatimah Kartini T. A. Aziz - T. A. Aziz, Tengku Norfatimah Kartini (2008)
COPD is one of the leading causes of death world wide, with an increasing prevalence and mortality. Asthma is also worldwide public health problem affecting about 300 million people. The main objective of this study was to describe trends or patterns in the consumption of drugs for the treatment of Obstructive Airway Disease (OAD). The retrospective study was conducted in outpatient pharmacy department (OPD), Hospital Tengku Ampuan Rahimah (HT AR), Klang. The data were collected for 3 relative months, which were May, June and August. All data collected were analyzed using Microsoft Excel programs and SPSS software (Version 12.0). Prescription of drugs for OAD in the OPD HTAR increased between May and June 2008, but slightly decreased in August 2008. In HT AR, the used of combined inhaler of long acting /h-adrenergic agonists with corticosteroids and other combinations was relatively small in number. The number of patients treated with short-acting /h-agonists decreased slightly from May to June. The consumption percentage of xanthines such as theophyllin were very small, (0.15%). The trends or pattern in the consumption of drugs for the treatment of OAD in HTAR for three selective months were relatively similar.